2016
DOI: 10.1111/gcbb.12297
|View full text |Cite
|
Sign up to set email alerts
|

Winter oilseed production for biofuel in the US Corn Belt: opportunities and limitations

Abstract: Interest from the US commercial aviation industry and commitments established by the US Navy and Air Force to use renewable fuels has spurred interest in identifying and developing crops for renewable aviation fuel. Concern regarding greenhouse gas emissions associated with land-use change and shifting land grown for food to feedstock production for fuel has encouraged the concept of intensifying current prominent cropping systems through various double cropping strategies. Camelina (Camelina sativa L.) and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 135 publications
0
57
0
Order By: Relevance
“…Moreover, winter annual types autumn-seeded have proven to be freeze-hardy in the northern United States (Gesch and Cermak, 2011;Johnson et al, 2017) and have been demonstrated to be successfully double and relay cropped with soybean [Glycine max (L.) Merr.] Integrating winter camelina as a cover crop into corn (Zea mays L.)-soybean systems has the potential to sustainably intensify crop production on millions of hectares across the US Corn Belt (Sindelar et al, 2017). Integrating winter camelina as a cover crop into corn (Zea mays L.)-soybean systems has the potential to sustainably intensify crop production on millions of hectares across the US Corn Belt (Sindelar et al, 2017).…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, winter annual types autumn-seeded have proven to be freeze-hardy in the northern United States (Gesch and Cermak, 2011;Johnson et al, 2017) and have been demonstrated to be successfully double and relay cropped with soybean [Glycine max (L.) Merr.] Integrating winter camelina as a cover crop into corn (Zea mays L.)-soybean systems has the potential to sustainably intensify crop production on millions of hectares across the US Corn Belt (Sindelar et al, 2017). Integrating winter camelina as a cover crop into corn (Zea mays L.)-soybean systems has the potential to sustainably intensify crop production on millions of hectares across the US Corn Belt (Sindelar et al, 2017).…”
Section: Researchmentioning
confidence: 99%
“…and other shortseason summer crops because of their early maturity Berti et al, 2015;Johnson et al, 2017). Integrating winter camelina as a cover crop into corn (Zea mays L.)-soybean systems has the potential to sustainably intensify crop production on millions of hectares across the US Corn Belt (Sindelar et al, 2017). As a cover crop, winter camelina provides several ecosystem services including soil protection, improved water quality, and forage for pollinators (Eberle et al, 2015;Berti et al, 2017;Johnson et al, 2017), with the added benefit of harvesting its seed for economic return.…”
mentioning
confidence: 99%
“…Regression modeling estimated 112 to 151 Tg year −1 of rye biomass could be harvested for bioenergy purposes in continuous corn and corn-soybean rotations in the US Corn Belt [126]. Further, incorporation of winter oilseeds into corn-soybean cropping systems may provide additional farm revenue while providing numerous ecosystem services (e.g., increased biodiversity, soil protection, food source for pollinators) [127].…”
Section: Other Considerationsmentioning
confidence: 99%
“…A 3-yr rotation of corn-corn-soybean [Glycine max (L.) Merr.] is widespread in the US Corn Belt, particularly in central Nebraska, northern Iowa, and northern Illinois (Sindelar et al, 2015). In addition to its use for the livestock industry, corn residue is the primary feedstock for the fledgling cellulosic bioenergy industry (Mitchell et al, 2016 …”
mentioning
confidence: 99%